Challenges to occupational medicine in view of the problem of work-related diseases and the aging of workforce. Directions for further development and intentional changes in preventive care of employees in Poland - Andrzej Marcinkiewicz; Jolanta Walusiak-Skorupa; Marta Wiszniewska; Marcin Rybacki; Wojciech Hanke; Konrad Rydzyński (Nofer Institute of Occupational Medicine, 2016)
The system of occupational health care in Poland, based on occupational medicine service, takes care of almost 12.5 million employees subjected to over 4.5 million obligatory periodic medical check ups. This form of providing prophylactic care comes down to examinations dictated by legal regulations, whose scope is not oriented towards a comprehensive workers' health assessment, but to the examination of the systems and organs critical to work-related dangers. Simultaneously, epidemiological data indicate a large number of chronic diseases, which may influence the professional activity, like hypertension or diabetes and a high percentage of patients not aware of their illness. Since patients participating in obligatory examinations usually feel healthy and do not use health care services on a daily basis, an occupational medicine physician has a unique opportunity to detect health disorders at an early stage, which can prevent the development of health complications affecting the condition of the patient, limiting their professional activity, but also causing additional costs of the health care system. The authors have proven the need to involve occupational medicine services in the prevention of chronic diseases and the need to introduce additional sources of financing for procedures enabling early detection of diseases the patient may not be aware of or control of the effectiveness of already diagnosed illnesses. They addressed the need to change the current legal form of establishing and announcing the range of examinations and directives for certifying the lack or presence of health contraindications to work to the specified and updated standards prepared by scientific research institutes and occupational medicine societies. Med Pr 2016;67(5):691-700